(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Applying Religious Freedom and Authenticity in the Deconstruction of Sacred and Liturgical Practices in the Emergent Christianity Movement The expression of the post-modern concern for authenticity and the assumption of individual freedom in religious life is articulated in the avant-garde movement of emerging Christianity, and its emergent churches. Within this movement, the fundamental components of religious deconstructed, and of these the deconstruction of sacred space will be examined.